METODE PENDIDIKAN ISLAM MASA KINI DALAM KELUARGA PERSPEKTIF ABDULLAH NASHIH ULWAN - Setiawan, Agus; Kurniawanto, Eko (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2016)
This study describes the method of Islamic education in the family according to Abdullah Nashih Ulwan and relevance to education today. Approach in this research is library research. Abdullah Nashih Ulwan is a scholar who is an expert on Islamic education, anyone who wants a tarbiyah book and a discussion of modern problems is certainly not familiar to him. Abdullah Nashih Ulwan was born in 1928 AD In the Qadhi Askar area located in Bandar Halb, Syria. He grew up in a family that cling to religion and attach importance to Islamic morality in the association and muamalat fellow human beings. Abdullah Nashih Ulwan based all his ideas and thoughts on the Qur'an and the hadith of the Prophet. Then illustrates his explanation of what the Prophet did, his companions and salafs who were as good as a Sunni and an activity within the Muslim Brotherhood's organization, almost did not take the reference of Western thinkers except under certain circumstances, the thought was influenced by the thought of jama 'Ah. Ikhwanul Muslimin, he is an activist in the organization. The result of this study of Islamic education in its implementation requires appropriate methods to deliver educational activities towards the desired goals. However good and perfect Islamic educational material will not mean anything, when it does not have the right method or way of transforming it. According to Abdullah Nashih Ulwan there are five methods, namely: education by example, education by habituation, education with wise counsel, education with attention and monitoring and education with appropriate rewards and punishments. Five methods of Islamic education in the family according to Abdullah Nashih Ulwan there is relevance to education today.